2022
DOI: 10.1038/s41524-022-00860-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning assisted design principle search for singlet fission: an example study of cibalackrot

Abstract: This work uses quantum chemistry calculations and machine learning to explore design rules for singlet fission in a chemical space of four million indigoid derivatives. We identify ~400,000 derivatives of 2,2′-diethenyl cibalackrot, which theoretically fulfil the energy conditions for exoergic singlet fission above the silicon band gap energy. Probing this database with a random forest classifier, we observe that small substituents with positive mesomeric effects and weak negative inductive effects reinforce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…The pure product was obtained as a colorless viscous liquid (1.85 g, 85%). 3,5-Di-tert-butylphenylacetyl Chloride (10). 49 A mixture of 3,5-ditert-butylphenylacetic acid (2.0 g, 8.1 mmol) and thionyl chloride (2.9 mL, 40.0 mmol) was refluxed (oil bath) for 2 h (CaCl 2 tube).…”
Section: -Butoxyphenylacetyl Chloride (9)mentioning
confidence: 99%
See 1 more Smart Citation
“…The pure product was obtained as a colorless viscous liquid (1.85 g, 85%). 3,5-Di-tert-butylphenylacetyl Chloride (10). 49 A mixture of 3,5-ditert-butylphenylacetic acid (2.0 g, 8.1 mmol) and thionyl chloride (2.9 mL, 40.0 mmol) was refluxed (oil bath) for 2 h (CaCl 2 tube).…”
Section: -Butoxyphenylacetyl Chloride (9)mentioning
confidence: 99%
“…Calculations for 1 predicted other possible packing motifs in which this problem would be avoided, and we wondered whether substituents could force 1 to pack better. One could also use substitution to increase the already nearly ideal 2.25/1.3 ratio of molecular S 1 to T 1 excitation energies ,, by reducing the latter to 1.2 eV, and this route might be worth pursuing in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical calculations can be used to quantify intermolecular interaction components and chemical reactions. In recent years, data-driven research has also been conducted to predict the properties of macroscopic aggregate systems from microscopic molecular data. Inspired by the motivation to build a sustainable society (e.g., development of new materials for carbon-neutral processes, early diagnosis and treatment of diseases to improve human health and longevity, and the effective use of resources to improve productivity), several successful experimental studies based on simulation results have been reported. There is no doubt that experiments backed by simulations will become the standard for future chemical research.…”
Section: Introductionmentioning
confidence: 99%
“…The sturdy indigoid industrial dye known as cibalackrot (7,14-diphenyldiindolo[3,2,1-de:3',2',1'ij] [1,5]naphthyridine-6,13-dione, 1), 1,2 and its analogs containing thienyl instead of phenyl groups 3,4 have been of potential interest as organic electronic, 5,6 photonic, 7 and singlet fission 3,8,9,10,11,12 materials. Of particular appeal to us is singlet fission, 13 a process in which a singlet exciton splits into two triplet excitons, promising to overcome the Shockley-Queisser limit 14 of about 1/3 to single-junction solar cell efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations for 1 8 predicted other possible packing motifs in which this problem would be avoided, and we wondered whether substituents could force 1 to pack better. One could also use substitution to increase the already nearly ideal 2.25/1.3 ratio of molecular S 1 to T 1 excitation energies 3,9,10 by reducing the latter to 1.2 eV, and this route might be worth pursuing in the future. 3,5-dibromotoluene (15) into Grignard reagents and treating them with D 2 O to obtain toluene-4-d ( 16) 27 and toluene-3,5-d 2 (17).…”
Section: Introductionmentioning
confidence: 99%